Plea Bargaining as a Solution for Criminal Case Backlog in Indonesia - Hakim , Lukman; Zulhuda, Sonny (International Journal of Psychosocial Rehabilitation, 2020)
The criminal justice system in Indonesia has not been able to overcome the criminal case backlog in courts. Besides the report from the Supreme Court about the large backlog of criminal cases in judicial institutions, there was also research that showed that judges in Indonesia tend to arrive at guilty verdicts on criminal acts with minor criminal charges (sanction under 5 years). The concept of plea bargaining, which has been known and applied in several countries, will also be included in Article 198, paragraph (5), and 199 of the Draft of Criminal Procedure Code (RKUHAP) in Indonesia, which will be made law. Although non-explicit verb is named as plea bargaining, the spirit of these articles is similar to the plea bargaining system, which has been practiced in many countries and is considered successful in overcoming the criminal case backlog in courts; therefore, the study uses a comparative study of the plea bargaining system in several countries and also uses a normative research method and is carried out by using the statutory approach through a review of laws and regulations as well as regulations relating to the issue discussed. Legal materials are obtained from the Criminal Procedure Code (KUHAP) and the Draft of Criminal Procedure Code (RKUHAP), which has been in the final discussion at the House of Representatives and Government, and in addition, the secondary legal materials are obtained from books, journals, and other literature. Meanwhile, the data collection technique used is library research by examining legal materials relevant to the research discussion.